Overview of Impella and mechanical devices in cardiogenic shock. (3rd April 2018) - Chera, Hymie Habib; Nagar, Menachem; Chang, Nai-Lun; Morales-Mangual, Carlos; Dous, George; Marmur, Jonathan D.; Ihsan, Muhammad; Madaj, Paul; Rosen, Yitzhak
ABSTRACT: Introduction : Cardiogenic shock (CS) is a life-threatening condition associated with significant morbidity and mortality. The Impella (Abiomed Inc.) is an axial flow pump on a pigtail catheter that is placed across the aortic valve to unload the left ventricle by delivering non-pulsatile blood flow to the ascending aorta. It is used for high-risk percutaneous coronary intervention and CS. Areas covered : Percutaneous mechanical support devices are placed in a minimally invasive manner and provide life-saving assistance. We review Impella and other percutaneous devices such as intra-aortic balloon pump, TandemHeart, and extracorporeal membrane oxygenation (ECMO) and the evidence supporting their use in the setting of CS. Expert commentary : Impella has been proven to be safe and may be superior to other mechanical support devices in CS.